Electrical bioimpedance spectroscopy measurement of polyphenols in three Colombian passifloras (2019)
Fruits and vegetables in the daily diet offer protective action against free radicals, inflammatory agents, and fungi. Polyphenols, found in these natural products, have been studied in order to understand their contribution to the prevention of multiple diseases. The identification and quantification of polyphenols have been evaluated uding the Folin-Ciocalteu method. This procedure requires several chemical reagents and different electrical devices, generating chemical waste and at great expense. There is a need to develop polyphenol identification and quantification techniques that are less costly and generate minimum contamination. Electrical bioimpedance spectroscopy (EBS) is a promising alternative that could contribute to measuring total polyphenol content in fresh fruits and vegetables. This study focused on using EBS and characterizing electrical response in fruit pulp from three different Colombian passifloras. The study aimed to compare the electrical parameter values of an Equivalent Electrical Model (EEM) to the total polyphenol content quantified by the FolinCiocalteu method.